2019
DOI: 10.3390/jcm8020158
|View full text |Cite
|
Sign up to set email alerts
|

Origanum majorana Essential Oil Inhalation during Neurofeedback Training Reduces Saliva Myeloperoxidase Activity at Session-1 in Bruxistic Patients

Abstract: Introduction: Bruxism affects teeth and provokes sleep alterations. We evaluated whether saliva Myeloperoxidase (MPO) activity could be reduced after 21 neurofeedback training (NO) sessions in Origanum majorana (AE) bruxistic-treated patients (n = 12 patients, 120 saliva samples). The term divergence evaluates cerebral activity, which was compared between bruxistic patients with/without this essential oil exposure during 21 NO training sessions (n = 12, n = 120 saliva samples). The nasal filter used allow us t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
(95 reference statements)
0
2
0
1
Order By: Relevance
“…Recently, a group of researchers demonstrated that Origanum majorana essential oil (OmEO) exerted antidepressant-like effects by modulating noradrenergic, dopaminergic, and serotonergic systems [ 18 ]. Another group of researchers showed that OmEO alleviated anxiety in bruxistic patients and claimed that this essential oil might represent a safe alternative for benzodiazepine treatment [ 19 ]. Moreover, O. majorana possesses anti-inflammatory properties [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a group of researchers demonstrated that Origanum majorana essential oil (OmEO) exerted antidepressant-like effects by modulating noradrenergic, dopaminergic, and serotonergic systems [ 18 ]. Another group of researchers showed that OmEO alleviated anxiety in bruxistic patients and claimed that this essential oil might represent a safe alternative for benzodiazepine treatment [ 19 ]. Moreover, O. majorana possesses anti-inflammatory properties [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…e sálvia (Salvia sclarea L.) promove alívio da dor provocada pela dismenorreia primária [38] . O óleo essencial de Origanum majorana aumentou o efeito ansiolítico em pacientes portadores de bruxismo [39] . Os resultados levantados por Erenler et al [40] mostraram que o extrato de O. majorana L. exibiram atividades antioxidantes significativas.…”
Section: Capim Cidreiraunclassified
“…Recently, the popularity of herbal remedies has increased due to their easy access, fewer complications, unique diversity of chemical structures, and biological activities (9). Medicinal plant aromas were shown to be effective in improving hemodynamic variables and treating stress and anxiety in several studies (10)(11)(12). Aromatherapy and the use of medicinal plant oils in reducing anxiety have long been considered in traditional medicine.…”
Section: Introductionmentioning
confidence: 99%